Analysis of Risk Management Implementation in A Holding Company: Infrastructure, Resources, and Risk Management Governance - Hasan, Hasbiyallah; Priyarsono, Dominicus Savio; Ramadyanto, Widodo (Dinasti Publisher, 2024)
X is a state-owned enterprise operating as a holding company across various industries. In 2022, X's total consolidated assets reached Rp 49.1 trillion, encompassing financial services, industrial estates, construction, water management, media, and technology. The expansion into a conglomerate brings challenges and uncertainties, necessitating a systematic risk management process, as accommodated by the regulations in Minister of SOE Regulation Number 2 of 2023 on Guidelines for Governance and Significant Corporate Activities of State-Owned Enterprises. This research focuses on analyzing the alignment and identifying gaps in X's risk management practices based on this regulation, as well as proposing steps to enhance risk management effectiveness in X to face business challenges. The study employs a triangulation approach through document observation, interviews, and literature review. The findings reveal several gaps in the implementation of risk management at X, highlighting areas for improvement, including three lines of defense implementation, enhancing a risk-aware culture, ensuring the independence of the risk management function in its subsidiaries, involving and evaluating the roles of the board of commissioners and the director of risk management, and optimizing the integration process of risk management with its subsidiaries, both in policy and practice